Optimising Radium 223 Therapy for Metastatic Castration-Resistant Prostate Cancer –5-year Real-World Outcome: Focusing on Treatment Sequence and Quality of Life. Issue 10 (October 2020) - Jiang, X.Y.; Atkinson, S.; Pearson, R.; Leaning, D.; Cumming, S.; Burns, A.; Azzabi, A.; Frew, J.; McMenemin, R.; Pedley, I.D.
Abstract: Aims: Real-world evidence of radium 223 (Ra-223) for the treatment of men with metastatic castration-resistant prostate cancer is emerging. In this prospective single-centre service evaluation, we report for the first time in the UK, real-world quality of life (QoL) and survival outcomes, including the sequencing impact, in 228 treated patients. We aim to share our 5-year experience on how to optimise Ra-223 treatment. Materials and methods: Patients who received Ra-223 therapy between 2014 and 2018 at the Northern Centre for Cancer Care, Newcastle upon Tyne, UK were included in this evaluation. Demographics, clinical characteristics, blood parameters, treatment sequencing and QoL data using abbreviated Functional Assessment of Cancer Therapy-Prostate questionnaires were prospectively collected and analysed. Results: In total, 228 patients were included; median age 72 years (51–87). The medium overall survival was 11.1 months. Overall survival in post-chemotherapy and chemotherapy-naïve patients was 8.1 and 12.3 months, respectively ( P = 0.02, hazard ratio 1.52, 95% confidence interval 1.06–2.17); in pre-enzalutamide and post-enzalutamide patients was 11.3 and 10.4 months, respectively ( P = 0.65, hazard ratio 0.92, 95% confidence interval 0.63–1.33); in pre-abiraterone and prednisolone and post-abiraterone and prednisolone patients was 11.8 and 10.5 months, respectively ( P = 0.08, hazard ratio 0.74, 95% confidence interval 0.51–1.06); in this latter group, the fracture rate was 24% (15/63). QoL post Ra-223 ( n = 101 evaluated) showed that pain scores improved in 54%, there was no change in 17% and pain scores worsened in 30% of treated patients. Overall QoL scores showed a similar trend. QoL was not significantly associated with overall survival. Conclusions: Ra-223 palliates pain and improves disease-related QoL in most patients in the real-world setting. Our survival outcome is comparable with other real-world studies. Chemotherapy-naïve patients seemed to have better survival than those who received prior chemotherapy. No significant survival differences were observed between pre- and post-abiraterone and prednisolone or enzalutamide patients. The fracture rate in the post-abiraterone and prednisolone group seemed to be high. Bone health evaluation and protection should be incorporated as standard of care. Highlights: Radium 223 (Ra-223) palliates pain and improves disease-related quality of life (QoL) in most treated patients in the real-world setting. Post Ra-223 therapy, prostate-specific antigen (PSA) reduction (≥30 %) is a better predictor than ALP reduction (≥30 %) for QoL improvement. Chemotherapy-naïve patients seemed to have a better survival outcome than those who received chemotherapy prior to Ra-223. Compared with ERA223 control cohort (placebo+ abiraterone and predinisolone), fracture rate remains elevated in men treated with Ra-223 sequentially post-abiraterone and prednislone. Fitness but not age was significant in predicting better survival outcome.